Characteristics of Actinomyces spp. and Nocardia spp. simulating neoplasia - Dall Bello, Aline Gehlen (2015)
Introduction: Actinomyces and Nocardia are filamentous bacteria that can simulate neoplastic diseases, mainly in lungs.Methods: A retrospective study based on the analysis of the medical records of five cases of actinomycosis and nocardiosis, which has been primarily misdiagnosed as lung cancer according to their radiographic findings. Cases were selected from a sample of 38 patients diagnosed with actinomycosis and 29 patients diagnosed with nocardiosis at the Mycology Laboratory of Irmandade de Misericórdia Santa Casa de Porto Alegre (state of Rio Grande do Sul, Brazil) between January 1977 to December 2012. The diagnosis was established by culture and histological examination. The literature was also critically reviewed.Results: We reported data of three cases of nocardiosis and two cases of actinomycosis that was primary diagnosed as lung cancer. The patients’ mean age was 50.6 (ranged from 43-63), four were male and 80% (4/5) of patients were immunocompetent. In more than 50% of patients, diagnosis and also treatment of lesions required surgical intervention. Conclusions: The complete knowledge of disease manifestations accelerates diagnosis and treatment and decreases unnecessary surgical interventions and morbidity and mortality rates, which are high in these infections.